(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
This article examines the operations of enterprises providing outsourcing services for the feeding of military personnel. Through an analysis of various models, methods, and performance metrics, the paper aims to understand the benefits and limitations of outsourcing in this sector. The research provides insights into efficiency, cost-effectiveness, and service quality, with conclusions guiding future improvements for military feeding services.